Preparation method of lithium slag fine aggregate and building cementing material
By adding granular materials to lithium mica raw materials, granular lithium clinker is formed in the lithium extraction process, and the lithium slag fine aggregate is separated by water washing and filtration, solving the problem of complex lithium slag treatment process and insufficient resource utilization is insufficient. , realizes process simplification and efficient resource utilization.
Patent Information
- Application Number
- CN202411346402.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, the process of lithium slag is complex, consumes a lot of energy and water resources, and additional processing steps are required to separate useful components.
By adding granular material to the lithium mica raw material, granular lithium clinker is formed during the calcination process of the lithium extraction process, and then washed and filtered to separate the lithium slag fine aggregate, saving the complexity of additional treatment.
The process flow is simplified, equipment investment, energy consumption and labor costs are saved, production cycle is shortened, production efficiency is improved, and the resource utilization of lithium slag is realized.
Smart Images

Figure CN119409433A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to a method for preparing lithium slag fine aggregate and building cementitious materials. Background Art
[0002] Lithium has many excellent electrical and metallic properties. It is a rapidly developing emerging material and a material for the future. With the large-scale mining and smelting of lithium ore, a large number of by-products are produced. For example, the treatment of lithium slag is an industry pain point that needs to be solved urgently.
[0003] At present, lithium slag generated during lithium extraction is usually subjected to additional treatment, such as crushing, screening, washing, dehydration, harmless treatment, modification, etc., before being used in building materials such as concrete and mortar. These processes not only increase the complexity of the treatment process, but also consume a lot of energy and water resources. Summary of the invention
[0004] The present application provides a method for preparing lithium slag fine aggregate and building cementitious materials which is conducive to simplifying the process.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing lithium slag fine aggregate, and the method for preparing fine aggregate for concrete mortar comprises:
[0006] The lithium raw material and the granulation material are mixed evenly according to a preset ratio to form a mixed material;
[0007] The mixed material is fed into a rotary kiln for calcination to form granular lithium clinker;
[0008] The calcined granular lithium clinker is washed and filtered to separate lithium-containing brine and fine aggregate; wherein the lithium-containing brine can be used for lithium extraction.
[0009] According to the first aspect, in a possible implementation manner, the fineness modulus of the fine aggregate is 1.0 to 1.5.
[0010] According to the first aspect, in a possible implementation manner, the granulation material includes one or more of a siliceous mineral material, an aluminous mineral material, and a calcareous mineral material.
[0011] According to the first aspect, in a possible implementation manner, the granulation material includes one or more of quartz, kaolin, clay, montmorillonite, bentonite, limestone, calcium oxide, calcium hydroxide and calcium sulfate.
[0012] According to the first aspect, in a possible implementation manner, the fineness of the granulated material is 80 mesh to 200 mesh.
[0013] According to the first aspect, in a possible implementation, the amount of granulation material added is 1% to 15%.
[0014] According to the first aspect, in a possible implementation, in the step of feeding the mixed material into a rotary kiln for calcining to form granular lithium clinker, the calcination temperature is 900° C. to 1150° C., and the calcination time is 20 min to 60 min.
[0015] In a second aspect, the present application also provides a method for preparing a building cementitious material, the method for preparing the building cementitious material comprising:
[0016] Mixing the fine aggregate prepared by the method according to the first aspect with coarse sand to form medium sand;
[0017] The medium sand is mixed with cement, mineral powder, fly ash, gravel and water to produce concrete; or the medium sand is mixed with cement, mineral powder, fly ash and water to produce mortar.
[0018] According to the second aspect, in a possible implementation, the coarse sand includes machine-made sand and / or river sand, and the fineness modulus of the coarse sand is greater than 3.0.
[0019] According to the second aspect, in a possible implementation manner, the proportion of fine aggregate in the medium sand product is 1%-50%.
[0020] The present application provides a method for preparing lithium slag fine aggregate and building cementitious material, wherein granulating material is added to lithium mica raw material, and granular lithium clinker is directly formed during the calcination process of lithium extraction process, and the granular lithium slag after washing the granular lithium clinker is lithium slag fine aggregate, which saves the complicated step of additional treatment of lithium slag. This not only saves equipment investment, energy consumption and labor cost, but also shortens the production cycle and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 It is a schematic flow chart of a method for preparing lithium slag fine aggregate in one embodiment of the present application;
[0023] Figure 2 It is a schematic diagram of a process for preparing a building cementitious material in one embodiment of the present application. DETAILED DESCRIPTION
[0024] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0025] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0027] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0028] The present application provides a method for preparing fine aggregate for concrete mortar, aiming to simplify the process.
[0029] In one embodiment, if Figure 1 As shown, the method for preparing fine aggregate for concrete mortar comprises:
[0030] Step S10, mixing the lithium raw material and the granulation material in a preset ratio to form a mixed material;
[0031] Lithium raw materials are raw materials containing lithium elements, which may be natural minerals or compounds that have undergone preliminary processing, such as lithium mica.
[0032] The granulation material may include one or more of a siliceous mineral material, an aluminous mineral material and a calcareous mineral material. The siliceous mineral material provides a stable skeleton structure, which helps to form and maintain the particles. The aluminous mineral material has a cohesive property, which can promote the bonding between the particles. The calcareous mineral material may react with other components during the calcination process to form a new mineral phase, thereby changing the properties of the particles.
[0033] Siliceous mineral materials include quartz, aluminum mineral materials include kaolin, clay, montmorillonite, bentonite, and calcium mineral materials include limestone, calcium oxide, calcium hydroxide, and calcium sulfate. That is, the granulation material can include one or more of quartz, kaolin, clay, montmorillonite, bentonite, limestone, calcium oxide, calcium hydroxide, and calcium sulfate. These materials can play different roles in the calcination process, such as bonding, fluxing, and adjusting particle structure.
[0034] The fineness of the granulated material can be between 80 mesh and 200 mesh, ensuring that the granulated material and the lithium raw material can be fully mixed and evenly distributed during the calcination process, thereby forming a uniform particle structure.
[0035] The selection of the mixing ratio depends on the required fine aggregate properties and the properties of the lithium raw material and granulation materials. Too low an addition may not be enough to form a stable particle structure, while too high an addition may reduce the lithium content of the final product or increase the cost. Generally speaking, the addition of granulation materials should be controlled between 1% and 15% of the weight of the lithium raw material. The selection of this range is intended to balance the formability, strength and lithium content of the particles.
[0036] Lithium raw materials and granulated materials can be mixed in special mixing equipment, such as ball mills, mixers, etc. These equipment can provide sufficient shear force and dispersing force to ensure that the lithium raw materials and granulated materials are fully stirred and dispersed during the mixing process. The length of mixing time depends on the type of mixing equipment, the nature of the mixture and the required mixing uniformity. Generally, sufficient time is required to ensure that all components are evenly distributed to avoid local agglomeration or stratification.
[0037] Step S20, sending the mixed material into a rotary kiln for calcination to form granular lithium clinker;
[0038] When the mixed materials enter the rotary kiln, as the temperature in the kiln gradually increases, some components in the granulation materials (such as silicates and aluminates in clay) begin to melt or soften, forming a liquid phase with a certain viscosity. These liquid phases play a vital role in the calcination process. They can wet and bond the surrounding particles (such as mica fragments, lithium raw material particles, etc.), providing the necessary conditions for the aggregation of particles.
[0039] When the mixed materials enter the rotary kiln, as the temperature gradually rises, some components in the granulation material (such as silicates and aluminates in clay) begin to melt or soften, forming a liquid phase with a certain viscosity. These liquid phases can wet and bond the surrounding particles (such as mica fragments, lithium raw material particles, etc.), causing them to gradually aggregate into larger particle clusters. Under the bonding effect of the liquid phase, the surrounding particles begin to gradually aggregate into larger particle clusters.
[0040] The rotation of the rotary kiln plays a key role in this process. The rotation not only ensures that the mixed materials are evenly heated in the kiln, but also causes the forming particles to roll, collide and rub in the kiln through the action of centrifugal force and gravity. This dynamic process helps the particles gradually adjust their shape, tending to form a smoother and more uniform granular lithium clinker.
[0041] The choice of calcination temperature and time has an important influence on the morphology and properties of the final particles. Generally speaking, the calcination temperature needs to be high enough to induce the desired chemical reactions and physical changes, such as the formation of a liquid phase and the aggregation of particles. However, too high a temperature may cause the particles to sinter excessively or melt, thereby destroying their near-spherical morphology and properties. Therefore, the calcination temperature is usually controlled between 900°C and 1150°C.
[0042] Likewise, the calcination time needs to be long enough to ensure that all particles are fully reacted and formed. However, too long a time may waste energy or cause excessive attrition of the particles. Therefore, the calcination time is generally controlled between 20 minutes and 60 minutes, depending on the composition of the mix, the temperature distribution in the kiln, and the desired particle properties.
[0043] The calcination time needs to be long enough to ensure that all particles are fully reacted and formed, but not too long as to waste energy or cause excessive attrition of the particles.
[0044] Step S30: washing and filtering the calcined granular lithium clinker to separate lithium-containing brine and fine aggregates. The lithium-containing brine can be used to extract lithium.
[0045] The granular lithium clinker formed after calcination is sent to a water washing and filtration system for treatment. The impurities and soluble components on the surface of the particles are removed by water washing, and the brine containing lithium elements and granular lithium slag are separated.
[0046] The granular lithium slag is fully contacted with water in the water washing equipment and cleaned by spraying, soaking or stirring. In this process, the soluble components on the surface of the particles (such as lithium-containing halides, silicates, etc.) are dissolved into the water to form lithium-containing brine.
[0047] After washing, the granular lithium slag and liquid mixture are separated into solid and liquid through a filtration device. Commonly used filtration equipment includes vibrating screens, filter presses or centrifuges. During the filtration process, the granular lithium slag is retained on the filter medium to form a filter cake or filter layer; while the lithium-containing brine flows out through the filter medium and enters the collection system.
[0048] Optimization of the water washing and filtration process ensures the purity and quality of the fine aggregate. The filtered granular lithium slag needs to be dried to remove residual moisture to form lithium slag fine aggregate. The drying method can be natural air drying or hot air drying, depending on production conditions and needs. The dried fine aggregate can be stored or further processed as a raw material for building materials or other purposes. The separated fine aggregate is also nearly spherical. The nearly spherical particle shape gives the fine aggregate excellent fluidity and filling efficiency, which helps to improve its application performance in building materials and other fields. The lithium-containing brine is collected for subsequent lithium extraction processes. The lithium extraction process usually includes methods such as evaporation crystallization, solvent extraction, ion exchange or membrane separation to extract high-purity lithium compounds from the brine.
[0049] In traditional methods, the generation of lithium slag often requires additional treatment after the lithium extraction process, such as crushing, screening, etc., to separate useful components or remove impurities. However, the present application forms granular lithium clinker directly during the calcination process of the lithium extraction process by adding granulating materials to the lithium mica raw material. The granular lithium slag after washing the granular lithium clinker is the lithium slag fine aggregate, which eliminates the complex process of additional treatment of the lithium slag. This not only saves equipment investment, energy consumption and labor costs, but also shortens the production cycle and improves production efficiency.
[0050] The small amount of harmful elements remaining in the lithium slag are directly solidified in the concrete, avoiding the pollution of these elements to the environment. At the same time, since the additional treatment process of lithium slag is omitted, the waste and pollutants that may be generated during the treatment process are also reduced. Converting lithium slag into valuable building materials (such as concrete fine aggregate) realizes the recycling of resources. This not only helps to reduce the exploitation and consumption of natural resources, but also helps to ease the pressure of waste disposal.
[0051] The fineness modulus of lithium slag fine aggregate is 1.0 to 1.5. A fineness modulus of 1.0 means that the proportion of fine particles in the lithium slag fine aggregate is relatively high, and the overall particle size is small, close to the category of ultra-fine sand. This kind of lithium slag fine aggregate has good filling performance in concrete or mortar, but attention should be paid to its possible impact on the strength and workability of concrete. A fineness modulus of 1.5 means that the particle size distribution in the lithium slag fine aggregate is more balanced, containing a certain proportion of slightly larger particles. Such lithium slag fine aggregate can provide good filling effect in concrete or mortar, while maintaining a certain skeleton effect, which helps to improve the overall performance of the material.
[0052] The fineness modulus of lithium slag fine aggregate is an important physical index, which reflects the coarseness of lithium slag fine aggregate particles. When the fineness modulus of lithium slag fine aggregate is lower than 1.0, it means that these particles are very fine and may contain a large number of particles smaller than a certain size, which may have an adverse effect on the performance of the material, such as increasing water demand and reducing strength.
[0053] In order to improve the performance of lithium slag fine aggregate, screening is usually used to remove excessively fine particles. The lithium slag fine aggregate is screened through a 200-mesh screen to adjust the particle size distribution of the lithium slag fine aggregate to make it more uniform, thereby improving the overall performance of concrete or building materials. At the same time, removing excessively fine particles can also reduce the water demand of the material and improve workability and strength.
[0054] In a second aspect, the present application also provides a method for preparing a building cementitious material, the method for preparing the building cementitious material comprising:
[0055] Step S100, mixing the lithium slag fine aggregate prepared by the method described in the first aspect with coarse sand to form medium sand;
[0056] The fine aggregate of lithium slag is mixed with coarse sand in a certain proportion to form medium sand. The mixing ratio can be adjusted according to the specific application requirements and material properties. The mixing process is usually carried out in a dedicated mixing equipment, such as a blender, drum mixer, etc., to ensure uniform mixing.
[0057] The coarse sand includes machine-made sand and / or river sand, and the fineness modulus of the coarse sand is greater than 3.0.
[0058] Machine-made sand is made by crushing and screening raw materials such as rocks and ores through mechanical equipment. It has the advantages of regular particle shape, good gradation and high cleanliness. It is one of the coarse aggregates commonly used in concrete and mortar. River sand is naturally formed, mainly from sediments in rivers, lakes and other waters. River sand has round particles, smooth surface, good fluidity and adhesion, and is also a coarse aggregate widely used in the construction industry.
[0059] Fineness modulus is an indicator to measure the coarseness of sand and reflects the particle size distribution of sand particles. Limited by the fineness modulus of sand provided by the market being greater than 3.0, and the high-quality sand resources being consumed in large quantities during the development of the construction industry in the past, it is difficult to obtain and the output is insufficient. As a result, the sand particles that are easy to obtain are relatively coarse and the particle size distribution is relatively large. As a result, the concrete produced from coarse sand has poor encapsulation and fluidity, which is not conducive to pumping construction.
[0060] The present application mixes the lithium slag-based fine aggregate prepared by the preparation method of lithium slag fine aggregate with the obtained coarse sand to form medium sand to improve the performance of concrete. Specifically, medium sand can reduce the amount of cement in concrete, while improving the strength and durability of concrete. In addition, medium sand can also improve the concrete's impermeability, freeze-thaw resistance and other properties. Improve construction efficiency: Medium sand has good fluidity, which can reduce the resistance of concrete during mixing, transportation and pouring, and improve construction efficiency. Reduce costs: Since the particle size gradation of medium sand is better and the porosity per unit volume is smaller, the amount and cost of raw materials can be reduced.
[0061] In medium sand products, the proportion of lithium slag fine aggregate is 1% to 50%. The addition of lithium slag fine aggregate can enhance the bonding force between medium sand particles, thereby improving the strength and durability of concrete. However, too high a proportion of lithium slag fine aggregate may cause the concrete to be too dense, affecting the permeability and curing effect of the cement paste. The proportion of lithium slag fine aggregate will also affect the working properties of concrete or mortar, such as fluidity, pumpability and smoothness. The right amount of lithium slag fine aggregate can improve these properties and make construction smoother.
[0062] The range of 1% to 50% of lithium slag fine aggregate ratio provided in this application is a relatively wide range, which allows for flexible adjustment according to different engineering requirements, material sources and cost considerations. For example, in situations where high strength and high durability are required, the proportion of lithium slag fine aggregate can be appropriately increased; while in projects with strict cost requirements, a lower fine aggregate ratio may be preferred.
[0063] Step S200: Mix the medium sand with cement, mineral powder, fly ash, gravel and water to produce concrete; or mix the medium sand with cement, mineral powder, fly ash and water to produce mortar.
[0064] Concrete and mortar are both important building materials. Concrete has high strength and durability and is suitable for the load-bearing part of the building structure. Mortar is mainly used to fill the gaps between masonry materials such as bricks and stones, playing the role of bonding and leveling.
[0065] In this application, the lithium slag fine aggregate generated during the lithium extraction process is used to process concrete and mortar, which fully utilizes the solid waste from lithium extraction. At the same time, the small amount of harmful elements remaining in the lithium slag will be directly solidified in the concrete, which has obvious environmental benefits. Thus, the resource-based, efficient and harmless utilization of lithium slag is achieved.
[0066] First embodiment:
[0067] 100 parts of raw lithium mica, 5 parts of kaolin powder and 5 parts of calcium sulfate powder are mixed evenly by a mixer to form a mixture. The mixed mixture is sent to a rotary kiln for calcination at a temperature of 970°C and a calcination time of 40 minutes. The calcined clinker is a nearly spherical particle. The nearly spherical particles are cooled, washed and filtered with water, and dehydrated to obtain granular lithium slag, which is lithium slag fine aggregate. The fineness modulus of lithium slag fine aggregate is 1.3.
[0068] 200 parts of lithium slag fine aggregate, 650 parts of machine-made sand, 1050 parts of crushed stone, 250 parts of cement, 120 parts of mineral powder, 11 parts of polycarboxylate water reducer and 125 parts of water were mixed thoroughly and uniformly to obtain concrete.
[0069] Under normal temperature conditions, the initial setting time of conventional concrete is generally controlled between 1h and 6h, while the final setting time is generally controlled between 3h and 24h. The initial setting time of concrete prepared by the preparation method of the above-mentioned building cementitious material of the present application is 9±1h, the final setting time is between 12±1h, and no cracks of various types are generated in the molded test blocks. That is, the setting time and shrinkage performance of the concrete prepared by the above-mentioned method of the present application are normal.
[0070] The mechanical properties of the concrete are shown in the following table:
[0071] 3 days strength 7 days strength 28 days strength 22.9MPa 34.6MPa 41.8MPa
[0072] Second embodiment:
[0073] 100 parts of raw lithium mica, 5 parts of external clay powder and 5 parts of external limestone powder are mixed evenly by a mixer to form a mixture. The mixed mixture is sent to a rotary kiln for calcination at a temperature of 960°C and a calcination time of 45 minutes. The calcined clinker is a nearly spherical particle. The nearly spherical particles are cooled, washed and filtered with water, and dehydrated to obtain granular lithium slag, which is lithium slag fine aggregate. The fineness modulus of lithium slag fine aggregate is 1.4.
[0074] Take 200 parts of lithium slag, 680 parts of machine-made sand, 1020 parts of crushed stone, 200 parts of cement, 100 parts of mineral powder, 50 parts of fly ash, 10 parts of polycarboxylate water reducer and 130 parts of water, mix them well and evenly to obtain concrete.
[0075] The setting time and shrinkage properties of the concrete are normal.
[0076] The mechanical properties of the concrete are shown in the following table:
[0077] 3-day compressive strength 7-day compressive strength 28 days compressive strength 18.6MPa 30.7MPa 37.1MPa
[0078] Third embodiment:
[0079] 100 parts of raw lithium mica, 5 parts of kaolin, 5 parts of clay powder and 3 parts of limestone powder are mixed evenly by a mixer to form a mixture. The mixed mixture is sent to a rotary kiln for calcination at a temperature of 970°C and a calcination time of 40 minutes. The calcined clinker is a nearly spherical particle. The nearly spherical particles are cooled, washed and filtered with water, and dehydrated to obtain granular lithium slag, which is lithium slag fine aggregate. The fineness modulus of lithium slag fine aggregate is 1.3.
[0080] 300 parts of lithium slag, 590 parts of machine-made sand, 1020 parts of crushed stone, 200 parts of cement, 130 parts of mineral powder, 80 parts of polycarboxylate water reducer and 150 parts of water were mixed thoroughly and uniformly to obtain concrete.
[0081] The setting time and shrinkage properties of the concrete are normal.
[0082] The mechanical properties of the concrete are shown in the following table:
[0083] 3-day compressive strength 7-day compressive strength 28 days compressive strength 15.3MPa 27.7MPa 33.2MPa
[0084] Fourth embodiment:
[0085] 100 parts of raw lithium mica, 5 parts of external quartz, 8 parts of bentonite powder and 3 parts of external slaked lime powder are mixed evenly by a mixer to form a mixture. The mixed mixture is sent to a rotary kiln for calcination at a temperature of 950°C and a calcination time of 50 minutes. The calcined clinker is a nearly spherical particle. The nearly spherical particles are cooled, washed and filtered with water, and dehydrated to obtain granular lithium slag, which is lithium slag fine aggregate. The fineness modulus of lithium slag fine aggregate is 1.1.
[0086] Take 30 parts of lithium slag, 70 parts of machine-made sand, 18 parts of cement, 2 parts of mineral powder, 1 part of cellulose ether, 0.1 part of sodium dodecyl sulfate and 15 parts of water and mix them thoroughly to obtain mortar.
[0087] The setting time and shrinkage performance of the mortar are normal, and there is no cracking or hollowing after setting.
[0088] The mechanical properties of the mortar are shown in the following table:
[0089] 14 days bond strength 28 days compressive strength 0.26MPa 25.1MPa
[0090] Fifth embodiment:
[0091] 100 parts of raw lithium mica, 8 parts of external bentonite powder and 5 parts of external calcium sulfate powder are mixed evenly by a mixer to form a mixture. The mixed mixture is sent to a rotary kiln for calcination at a temperature of 940°C and a calcination time of 60 minutes. The calcined clinker is a nearly spherical particle. The nearly spherical particles are cooled, washed and filtered with water, and dehydrated to obtain granular lithium slag, which is lithium slag fine aggregate. The fineness modulus of lithium slag fine aggregate is 1.2.
[0092] Take 50 parts of lithium slag, 30 parts of machine-made sand, 18 parts of cement, 2 parts of fly ash, 1 part of cellulose ether, 0.1 parts of sodium dodecyl sulfate and 16 parts of water and mix them thoroughly to obtain mortar.
[0093] The setting time and shrinkage performance of the mortar are normal, and there is no cracking or hollowing after setting.
[0094] The mechanical properties of the mortar are as follows:
[0095] 14 days bond strength 28 days compressive strength 0.25MPa 23.4MPa
[0096] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the method of the present invention, addition of auxiliary steps, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing lithium slag fine aggregate, characterized in that: The method for preparing fine aggregate for concrete mortar comprises: The lithium raw material and the granulation material are mixed evenly according to a preset ratio to form a mixed material; The mixed material is fed into a rotary kiln for calcination to form granular lithium clinker; The calcined granular lithium clinker is washed and filtered to separate lithium-containing brine and fine aggregate; wherein the lithium-containing brine can be used for lithium extraction.
2. The method for preparing fine aggregate for concrete mortar according to claim 1, characterized in that: The fineness modulus of the fine aggregate is 1.0 to 1.
5.
3. The method for preparing fine aggregate for concrete mortar according to claim 1, characterized in that: The granulation material includes one or more of a siliceous mineral material, an aluminous mineral material and a calcareous mineral material.
4. The method for preparing fine aggregate for concrete mortar according to claim 1, characterized in that: The granulation material includes one or more of quartz, kaolin, clay, montmorillonite, bentonite, limestone, calcium oxide, calcium hydroxide and calcium sulfate.
5. The method for preparing fine aggregate for concrete mortar according to claim 1, characterized in that: The fineness of the granulated material is 80 mesh to 200 mesh.
6. The method for preparing fine aggregate for concrete mortar according to claim 1, characterized in that: The amount of granulating material added is 1% to 15%.
7. The method for preparing fine aggregate for concrete mortar according to claim 3, characterized in that: In the step of feeding the mixed material into a rotary kiln for calcining to form granular lithium clinker, the calcining temperature is 900° C. to 1150° C., and the calcining time is 20 min to 60 min.
8. A method for preparing a building cementitious material, characterized in that: The preparation method of the building cementitious material comprises: Mixing the fine aggregate obtained by the method for preparing fine aggregate for concrete mortar according to any one of claims 1 to 7 with coarse sand to form medium sand; The medium sand is mixed with cement, mineral powder, fly ash, gravel and water to produce concrete; or the medium sand is mixed with cement, mineral powder, fly ash and water to produce mortar.
9. The method for preparing a building cementitious material according to claim 8, characterized in that: The coarse sand includes machine-made sand and / or river sand, and the fineness modulus of the coarse sand is greater than 3.
0.
10. The method for preparing a building cementitious material according to claim 1, characterized in that: The proportion of fine aggregate in the medium sand product is 1%-50%.